Sosialisasi dan Simulasi Kesiapsiagaan Bencana pada Masyarakat - Nugroho Nugroho; Nufa visca (Lembaga Pengembangan Kinerja Dosen, 2024)
Indonesia is one of the countries prone to disasters. Data from the Disaster Information Indonesia (DIBI) indicates that between 2019 and 2023, there were 15,928 disasters with 18,872,310 casualties. The high frequency of disaster occurrences and their impacts necessitates disaster preparedness. Generally, the readiness index of the Indonesian population in terms of emergency response is classified as inadequate. Tasikmalaya Regency ranks second among disaster-prone areas in Indonesia, with Cipatujah Subdistrict being the most vulnerable subdistrict within Tasikmalaya Regency. One of the vulnerable villages in Cipatujah Subdistrict is Sindangkerta Village. A dedicated team from the Faculty of Health Sciences at Siliwangi University, in coordination with the Tasikmalaya Regency Disaster Management Agency (BPBD Kabupaten Tasikmalaya) and in partnership with Dompet Dhuafa, conducted activities to raise awareness and simulate disaster preparedness. These activities took place on August 5, 2019, involving 46 students from vocational high schools in Sindangkerta. The awareness-raising activities utilized PowerPoint presentations and posters, while the simulation exercises were conducted in the field. The evaluation of the activities was carried out through real-time monitoring. The activities ran smoothly, as the participants actively engaged with enthusiasm and demonstrated a high level of curiosity.